Multilingualism in Education: A Poststructuralist Critique - MCNAMARA, TIM (The Modern language journal (Boulder, Colo.), 2011)
Discussions of multilingualism in education, as exemplified by the articles in this issue, can be critically reevaluated using perspectives available from poststructuralism. These perspectives focus on the potential ambiguity of language and language practices. This, in turn, encourages us to question simple notions of the relationship of learners to the languages they speak, especially the "mother tongue," to see the individual's relation to language as a relation to power, and to recognize the polyvalent role of language tests in the context of multilingual education as, on the one hand, enforcing the relations of power in language and, on the other, disrupting them. The article focuses on the extent to which these themes are acknowledged in the articles in this issue, exploring the impact of the contrasting contexts represented, and presents examples of other discussions, especially in colonial and postcolonial contexts, that reflect alternative views of multilingualism in education. These include Derrida's reflections on his own language socialization as a colonial subject in Algeria during the time of the Vichy regime and studies of the role of language in contemporary education systems in Africa and Southeast Asia.